2015
DOI: 10.1007/s00280-015-2841-5
|View full text |Cite
|
Sign up to set email alerts
|

First-line gefitinib treatment in elderly patients (aged ≥75 years) with non-small cell lung cancer harboring EGFR mutations

Abstract: First-line gefitinib could be a preferable standard treatment in elderly patients with advanced NSCLC harboring sensitive EGFR mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 25 publications
(36 reference statements)
0
12
0
Order By: Relevance
“…For elderly patients with NSCLC harboring EGFR mutations, first-line gefitinib and erlotinib also provide a high response rate (RR) and prolonged survival [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…For elderly patients with NSCLC harboring EGFR mutations, first-line gefitinib and erlotinib also provide a high response rate (RR) and prolonged survival [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, epidermal growth factor receptor (EGFR) mutations, such as exon 19 deletion and L858R point mutation, are well recognized as driver mutations and promising predictors of the efficacy of EGFR tyrosine kinase inhibitors (TKIs), such as gefitinib, erlotinib, and afatinib, in NSCLC patients harboring EGFR mutations [3][4][5][6][7]. In addition, EGFR-TKIs are recommended for elderly people [8][9][10] and they are effective regardless of the treatment timing in patients with NSCLC harboring EGFR mutations [11,12]. Recently, a large cohort study reported that gefitinib therapy resulted in a 5-year survival rate of approximately 20% in NSCLC patients harboring…”
Section: Introductionmentioning
confidence: 99%
“…EGFR-TKIs could prolong PFS, improve ORR and QoL, yet they have many side-effects, such as rash and diarrhea. [ 48 , 49 ] Taxanes also have several AEs: gastrointestinal reaction, alopecia, and hematological toxicity, particularly grade 3/4 leukopenia and neutropenia which tended to be more frequent after treatment with taxanes. [ 50 , 51 ] In the meta-analysis of this study, except for diarrhea and rash, there was a slightly worse trend toward EGFR-TKIs compared with taxanes.…”
Section: Discussionmentioning
confidence: 99%